Dynamic model of the temperature downstream to an indirect charge-air cooler considering heat losses to the environment. (25th July 2022) - Vagapov, Askar; Herzog, Alexander; Waiz, Andreas; Neumann, Philipp; Rohloff, Benjamin; Kabelac, Stephan
Abstract: Thermal management plays an increasingly important role for internal combustion engines due to the high demands on the transient response of vehicles and the legal requirements for pollutants. In particular, the goal to reduce exhaust-gas raw emissions while optimizing fuel consumption can be supported with the help of on-demand temperature control. One strategy to meet the thermal requirements connected to this consists of model-based approaches. For an implementation of such methods on an automotive electronic control unit, a sufficiently high accuracy has to be ensured by the underlying model, alongside the fulfillment of the real-time operation demand. In this publication, we suggest two analytical modeling approaches for heat exchangers with poor thermal isolation with respect to the surrounding. Here we lay a special focus on the real-time capability of the given algorithm for an automotive on-board application. To this end, we utilize the Hammerstein method which allows to divide the overall physical system into a nonlinear stationary part and a dynamical linear one. The former are based on the well-known concept for the dimensionless temperature change of heat exchangers, where we generalize this approach in order to take account of the heat-losses to the surrounding. We demonstrate our model for an indirect charge-air cooler in an internal combustion engine. For both models we find excellent accuracy, with an overall mean-absolute error of 1.23 K and 1.33 K respectively, when compared to experimental data sets containing measurements from the Worldwide harmonized Light Duty Test Procedure. Highlights: Dimensionless temperature change approach for heat exchangers subject to heat loss. Accurate dynamic real-time capable heat exchanger models for engine control units. Robust, versatile and numerically efficient method to describe heat exchangers.